Three New Sesquiterpenoids and One New Sesquiterpenoid Derivative from Chinese Eaglewood - Huan Zhao; Qinghua Peng; Zhuzhen Han; Li Yang; Zhengtao Wang (Molecules, 2016)
Three new sesquiterpenoids (1–3) and one new sesquiterpenoid derivative (4), along with three known sesquiterpenoids (5–7), were isolated from the 95% ethanolic extract of Chinese eaglewood [Aquilaria sinensis (Lour.) Gilg]. The structures of these compounds were elucidated through extensive analysis of spectroscopic data including IR, NMR, HRESIMS, and X-ray diffraction experiments. In addition, the above new compounds were detected for their bioactivities against LPS-induced NO production in RAW 264.7 cells. Among them, compound 2 exhibited obvious anti-inflammatory activity with an IC50 value of 8.1 μM.